A presença da literatura afro-brasileira na escola: uma proposta de intervenção para as aulas de língua portuguesa do 9º ano do ensino fundamental - Gonçalo, Sandra Regina Pereira (2015)
This work makes a significant approach to the presence of African-Brazilian literature in elementary education and more specifically a proposed intervention for the 9th year of Elementary School located in a town in the hinterland of Paraíba/PB. Such work as main objectives to discuss aspects related to official documents that underlie the law 10,639 / 03, to bring out the problematic insertion of African-Brazilian literature in the classrooms of elementary school and especially the 9th grade and suggest activities that may intervene practice of the Portuguese Language teachers in regard to the literature approach in the classroom. The study is based on the Federal Constitution of 1988, in the LDB, Law 10,639 / 03, texts and BEZERRA and COSTA, (2013); COSSON, (2014); PCN's / 1997; PLURALIDADE CULTURAL (1997); LEITE (2011) among others. The intervention proposal consisted of two questionnaires and five literary workshops in the classroom with students. These workshops were conducted as described order and numbering and questionnaires were administered one before and another after the workshops.